EFFECT OF ADDING NEOSTIGMINE TO LIDOCAINE ON THE ONSET OF EPIDURAL ANAESTHESIA (Iraqi Journal of Medical Sciences, 2016)
Background:Shortening the onset time of sensory block is a practical goal to improve the quality of epidural anesthesia. The addition of Neostigmine to a local anesthetic solution is one of the ways used during epidural anesthesia to perform this goal.Objective:To examine the onset time of sensory block and intensity of motor block during epidural lidocaine anesthesia with and without Neostigmine addition to the epidural solution and to compare haemodynamic changes and any associated side effects.Methods: We made two groups of twenty patients, each of both the sexes ranging from 20-80 years age group of American Society of Anaesthesia (ASA) Grade I & II, selected for abdominal surgery; group I (epidural administration of 17 ml of 2% Lidocaine plus 1 ml of normal saline); group II (epidural administration of 17 mL of 2% Lidocaine plus 500 µg Neostigmine in 1 ml of normal saline). The sensory block was assessed by pinprick method; the motor block was assessed by using Bromage scale. The hemodynamic changes, post epidural shivering, and side effects of epidural Neostigmine were also recorded.Results:The onset time of sensory block up to T10 dermatome was significantly more rapid in the group II (8.95±2.44 minutes) than that of the group I (25±4.32 minutes). The upper level of sensory block was also significantly higher in group II, regarding intense motor block it was significantly in group II (13.11± 5.52 minutes) while in group I it was 30.2± 6.4 minutes; this represents the stage of just being able to flex knee but full flexion of foot (Bromage Scale). Post epidural arterial blood pressures and heart rates were not statistically different between both groups. No significant difference was also noticed considering associated side effect (nausea, vomiting, hypotention and shivering).Conclusions:Addition of Neostigmine 500µg to 2% Lidocaine shortened the onset of sensory block with rapid cephaled spread with more potent motor block without increasing side effect.Key Words:Epidural, Neostigmine, Lidocaine, Onset of sensory block and Motor block.
Keywords: Epidural; Neostigmine; Lidocaine; Onset of sensory block and Motor block